Carotid Artery - Gender and Health - Luigi Fabrizio Rodella; Rita Rezzani (IntechOpen, 2019)
This book collects recent experimental and clinical studies on gender influence in carotid artery compliance in health and pathological states, discussing also the usefulness and appropriateness of specific and personal medical therapy. Additionally, it provides an overview of the growing importance of ongoing studies on the benefit and risk of gender-specific therapy.
English
Keywords: Medicine; Surgery; Vascular Surgery; Health Sciences